A aplicação da tecnologia blockchain no imposto sobre circulação de mercadorias e serviços - Valentina, Vitória Tavares Della (2022)
The present research aims to study blockchain technology and its applicability in the collection of Tax on the Circulation of Goods and Services, in order to seek greater efficiency in taxation and evaluate its ability to protect tax secrecy and taxpayers’ data. To do so, it uses the hypothetical-deductive approach method, starting from the assumptions that blockchain technology is applicable to tax law, is able to improve compliance with tax obligations in consumption tax and, finally, is able to provide security to taxpayer data. Moreover, the historical procedure is used, investigating the emergence of the institutes studied in the presente research, in order to verify their influente today, as well as the monographic method, with the deepening of the study about blockchain technology, the protection of taxpayers’ data and the Tax on the Circulation of Goods and Services. Finally, the research technique will be qualitative and theoretical, with an exploratory objective through the bibliographic research procedure, analyzing the production of Brazil and internacional doctrine on the subject. In this sense, the technological development until the creation of the blockchain and its pratical applications adopted in Latin America and the collection of Value Added Tax in the countries of Saudi Arabia and Indonesia, as well as the structuring of the network society, the phenomenon of the Fisco Data and the protection of personal data conferred by the national legal system, to then analyze the Tax on the Circulation of Goods and Services, starting from the origin of taxation, its evolution and basic principles, until reaching the complexity of the current National Tax System, including auxiliaries obligations. In view of this, it is concluded that there is room in the brazilian tax system for the aplication of blockchain technology in the relations between the tax authorities and the taxpayers, and that, due to its distributed structure, based on consensus and encryption, there is a guarantee of protection of the data of the taxpayers inserted in the network, however, it its equally concluded that the application of blockchain technology, by itself, as a tool, is not able to improve compliance with the tax obligations of the Taxo n the Circulation of Goods and Services, since, with the maintenance of the current legislation, there ill be the collection, now through the blockchain, of duplicate and excessive declarations.